The Image of the Creator in Ibn Rashiq’s Book “Al Omda” - Alhourani, Mohammad Issa (Opción, 2019)
The aim of the study is to investigate the image of the creator in Ibn Rashiq’s book entitled Al Omda via comparative qualitative research methods. As a result, the creator does not depart far from his linguistic meaning, through which he tries to capture the psychological, existential and intellectual aspects. In conclusion, Ibn Rashiq was largely consistent with critics of his time; his view came to the creator - like other old critics - focused on the psychological, moral and ethical aspects.